If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + y + -1x + 6y = 0 Reorder the terms: 12x + -1x + y + 6y = 0 Combine like terms: 12x + -1x = 11x 11x + y + 6y = 0 Combine like terms: y + 6y = 7y 11x + 7y = 0 Solving 11x + 7y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7y' to each side of the equation. 11x + 7y + -7y = 0 + -7y Combine like terms: 7y + -7y = 0 11x + 0 = 0 + -7y 11x = 0 + -7y Remove the zero: 11x = -7y Divide each side by '11'. x = -0.6363636364y Simplifying x = -0.6363636364y
| 7x-2x+2-x= | | 6n+10=-44 | | 2/3k=4/3 | | 4x^2+176=0 | | 8p-9=49 | | 2x^2+19+24=0 | | 2x/7-2x=x/2+17/2 | | 12/3+4-24/3x8 | | 5+(2-x)/3=7 | | K/4+5=4 | | 4x-9x=45 | | 2.5y-0.25y= | | -4=-1+c/5 | | 8m^2-2m=11 | | 4(2b+6)+11=-8b-13 | | 1/3x^2+4x-3=0 | | 3x-6=2x+2 | | 14j-6+8j-5= | | 3n-2+2n+5= | | 0=3b+27 | | a+2/a-1=a+11/a+4 | | b+12=-21 | | 1-2c-3c+100= | | 9y-8+4y= | | 3x/x^2 | | 9/540 | | ln(3x^2)-2x=0 | | 26+48x=-502 | | X=6-21 | | 10=n/6+9 | | -3(2t-2)+4t=7t-8 | | 6/174 |